Balanced Scorecard: uma proposta para aplicação em instituição de ensino superior - Morais, Marco Antonio Dantas de (2008)
The propose of the following presentation is to elaborate a structured model, based on the mission, vision, critical factors of success and strategic goals for a scholarship institution with no profitable ends. And to accomplish this, was selected the Balanced Scorecard as a tool that will help to propose a system of performance indicators totally fitted with the very strategic goals of this scholarship institution. This model of management, BSC, shall support the managers in the strict process of taking decisions, especially those that leads to the addressing of action and resources to the final accomplishment of the strategic objectives of the institution